Sensing the Danger Signals: cis-Jasmone Reduces Aphid Performance on Potato and Modulates the Magnitude of Released Volatiles - Sobhy, Islam S.; Caulfield, John C.; Pickett, John A.; Birkett, Michael A. (Frontiers in Ecology and Evolution, 2020)
In response to herbivory, plants synthesize and release variable mixtures of herbivore-induced plant volatiles (HIPVs) as indirect defense traits. Such induction of indirect plant defense can also be “switched on” by certain chemicals known as priming agents. Preceding work showed that the plant HIPV cis-jasmone (CJ) induced the emission of aphid defense-related volatiles affecting their behavioral response. However, little is known about the extent to which CJ-induced volatiles impacts aphid performance. In the current study, we conducted growth assays of potato aphids, Macrosiphum euphorbiae, observing their reproduction, development, and survival on CJ-primed potato plants. Adult M. euphoribae produced fewer neonates on CJ-treated plants compared to untreated plants. The weight and survival of M. euphorbiae reproduced neonates were significantly lower on CJ-treated plants. Additionally, there was a significant reduction in mean relative growth rate (MRGR) of M. euphoribae nymphs that fed on CJ-treated plants. Furthermore, the intrinsic rate of population increase (rm) of M. euphoribae was significantly reduced on CJ-treated plants. Volatile analysis showed that CJ treatment significantly increased the emission of differently assigned volatile groups that have functional or biosynthetic characteristics i.e. alcohols, benzenoids, homoterpenes, ketones, and sesquiterpenes at the all sampling periods. Such enhanced volatile emissions were persistent over 7 days, suggesting a long-lasting effect of CJ defense priming. A negative correlation was found between volatile emission and MRGR of M. euphoribae. Principal component analysis (PCA) of data for the volatiles showed that 6-methyl-5-hepten-2-one (MHO), (E)-4,8-dimethyl-1,3,7-nonatriene (DMNT) and (E,E)-4,8,12-trimethyl-1,3,7,11-tridecatetraene (TMTT) were the main volatiles contributing to the emitted blends, suggesting possible involvement in the reduced performance of M. euphorbiae. Overall, our findings demonstrate that priming potato with CJ significantly results in elevated emission of known biologically active volatiles, which may negatively impact aphid settling and other performance traits on primed plants.